STATE OF HAEMATOLOGICAL PARAMETERS IN THE CORRECTION OF ACUTE BLOOD LOSS WITH MAGNETITE NANOPARTICLES - Mokliak, Ye.V. (World of Medicine and Biology, 2014)
In the experiments in albino male rats it is shown that in acute posthemorrhagic anemia, the use of magnetite nanoparticles suspension (5-8 nm) prepared by electron-ray technology in the dose of 6.75 mg Fe/kg helps to normalize the total red blood cells count, hematocrit and hemoglobin at all terms of observation (3, 24, 72 hours and 5 days after blood loss) and increases the saturation of red blood cells by hemoglobin in the first 3 hours of compensation period after the blood exfusion.